CPWF Medium Term Plan (2010‐2012) - CGIAR Challenge Program on Water and Food (CGIAR Challenge Program on Water and Food, 2009)
This Medium Term Plan (MTP) is written as the CPWF transitions from its first Phase (2004‐ 2008) to its second Phase (2009‐2013). It describes the status of the CPWF as the newly established Board discusses and approves plans for this second Phase. At the time of writing three of six planned Stakeholder Consultations have been implemented. These were held in the Andean, Mekong and Nile basins. Contracts will be signed later this year for research in those basins. Stakeholder Consultations for the three remaining basins, Volta, Limpopo and Ganges, will be held later this year, with contracts to be signed in the first half of 2010. We consider the Phase 2 planning process a highlight of the CPWF 2009 programmatic achievements along with the many results coming out of the Phase 1 research portfolio that has fed into the plans contained in this document. In parallel has been the design of new program structures and procedures for carrying forward the CPWF research agenda. The CPWF’s External Review (CPER) Panel provided valuable advice and recommendations for the transition, as did the commentaries on the CPWF’s Phase 2 plans by IWMI and many other partners including ExCo, the Science Council (SC) in addition to the CPWF Consortium Steering Committee (CSC) and the CPWF Board.